USE OF ORGANIC VEGETABLES IN TYPICAL DISHES OF JAPANESE CUISINE - Cremasco, C. P.; Ohara, L.; Gabriel Filho, L. R. A.; Garcia, M. P. B.; Macini, N.; Putti, F. F.; Caneppele, F. L. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Recent studies have shown that organic food is safer and healthier than common food since the former is cultivated without any chemical fertilizers. Research at the Universidade Federal de Lavras, Brazil, has revealed that lettuce with organic fertilizers contains higher concentrations of phosphorus, potassium and magnesium when compared to lettuce with conventional fertilization. Research by the National Program in the Enhancement of Family Agriculture (PRONAF) has indicated higher nutritional rates in vegetables cultivated organically. Current paper is a statistical analysis on the consumption of Yakisoba (with organic products) at the trade fair in Presidente Prudente SP Brazil and identifies consumers´ knowledge on these organic products. Most yakisoba consumers are unaware of the organic products involved or believe that they are merely natural products, such as legumes, fruits and vegetables. People should be made aware of the importance of the products and their assets so that a higher demand may be established, production may be encouraged and their availability made possible at an affordable price for a larger number of people.